Left Atrioventricular Coupling Index as a Prognostic Marker of Cardiovascular Events: The MESA Study. Issue 3 (6th July 2021) - Pezel, Theo; Venkatesh, Bharath Ambale; De Vasconcellos, Henrique Doria; Kato, Yoko; Shabani, Mahsima; Xie, Eric; Heckbert, Susan R.; Post, Wendy S.; Shea, Steven J.; Allen, Norrina B.; Watson, Karol E.; Wu, Colin O.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Both left atrial and left ventricular functional parameters influence the prognosis of patients with cardiovascular diseases. This study aimed to investigate the prognostic value of a novel left atrioventricular coupling index (LACI) in a population without history of cardiovascular diseases at baseline. Participants of the Multi-Ethnic Study of Atherosclerosis who underwent a baseline cardiovascular magnetic resonance study were analyzed. LACI was defined by the ratio of the left atrial end-diastolic volume divided by the left ventricular end-diastolic volume. Cox proportional hazard models were used to evaluate the association between LACI and atrial fibrillation, heart failure, coronary heart disease death, and hard cardiovascular disease defined by myocardial infarction, resuscitated cardiac arrest, fatal and nonfatal stroke, or coronary heart disease death. Among the 4124 participants (61.5±10.1 years, 47.4% men), 1074 cardiovascular events were observed (mean follow-up, 13.0±3.2 years). Greater LACI was independently associated with atrial fibrillation (hazard ratio, 1.86 [95% CI, 1.69–2.04]), heart failure (hazard ratio, 1.50 [95% CI, 1.38–1.62]), hard cardiovascular disease (1.23 [95% CI, 1.13–1.34]), and coronary heart disease death (hazard ratio, 1.29 [95% CI, 1.15–1.45]; all P <0.0001). After adjustment for traditional cardiovascular risk factors, LACI showed significant improvement in model discrimination and reclassification compared with currently used standard models to predict outcomes. LACI is a strong predictor for the incidence of heart failure, atrial fibrillation, hard cardiovascular disease, and coronary heart disease death. LACI has incremental prognostic value to predict cardiovascular events over traditional risk factors and better discrimination and reclassification power compared with individual left atrial or left ventricular parameters.